Experimental Evidence for Abiotic Sulfurization of Marine Dissolved Organic Matter - Pohlabeln, Anika M.; Gomez-Saez, Gonzalo V.; Noriega-Ortega, Beatriz E.; Dittmar, Thorsten (Frontiers in Marine Science, 2017)
Dissolved organic sulfur (DOS) is the largest pool of organic sulfur in the oceans, and as such it is an important component of the global sulfur cycle. DOS in the ocean is resistant against microbial degradation and turns over on a millennium time scale. However, sources and mechanisms behind its stability are largely unknown. Here, we hypothesize that in sulfate-reducing sediments sulfur is abiotically incorporated into dissolved organic matter (DOM) and released to the ocean. We exposed natural seawater and the filtrate of a plankton culture to sulfidic conditions. Already after one hour at 20 °C, DOS concentrations had increased 4-fold in these experiments, and 14-fold after 4 weeks at 50 °C, indicating that organic matter does not need long residence times in natural sulfidic environments to be affected by sulfurization. Molecular analysis via ultrahigh-resolution mass spectrometry showed that sulfur was covalently and unselectively bound to DOM. Experimentally produced and natural DOS from sediments were highly similar on a molecular and structural level. By combining our data with published benthic DOC fluxes we estimate that 30 – 200 Tg DOS are annually transported from anaerobic and sulfate reducing sediments to the oceans. Uncertainties in this first speculative assessment are large. However, this first attempt illustrates that benthic DOS flux is potentially one order of magnitude larger than that via rivers indicating that this could balance the estimated global net removal of refractory DOS.